THE PERSONS NAMES BY PROFESSION OR OCCUPATION AS A SOURCE OF THE FORMATION OF THE FAMILY NAMES OF ZAPOROZHIAN COSSACKS (ON THE MATERIAL OF THE 1756 REGISTER OF THE ZAPOROZHIAN HOST) - Дзира, Іван (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The family names, which made from profession or occupation of a person, give interesting material not only for the study of the history of the Ukrainian language, but also for the reproduction of social-economic and ethnographic-domestic life both the Ukrainian lands and Zaporizhya particularly in the middle of XVIII cen. The purpose of the article consists in the research of the family names, which made from profession or occupation of the person, which presented in the official source of the middle of XVIII cen. The author set the tasks to elucidate the etymology of the derivative stems of the Zaporozhian nicknames, mark out their subject sub-groups, define the most productive sememas and the most widespread anthropolexemas. Results. In the register we exposed 343 family names, which contain man’s characteristic by profession or line occupation. The bearers of such nicknames are 1817 persons, that make up 12, 11% the general quantity of the register. The absolute majority of family names of this lexic-semantic group enters to composition of binominal anthroponymycal names proper (1791 bearer, 98,57% general quantity). The treatment of the historical context evidences, that the considerable part of the similar family names still had the appellative meaning. The family names of the investigated lexical-semantic group are subdivide into 18 sub-group. To the greatest by volume belong the sub-groups, which unite family names, which form in the connection with military service (35 anthropolexemas); agriculture, forestry, hunting and fishing (28 anthropolexemas); which reflects a division of labor in woodworking industry (28 anthropolexemas); commerce and different mediatory operations (27 anthropolexemas). The most active sememas: «коваль» (8 units), «піп» (8 units), «кравець» (6 units). The most spread were names Швець (234), Кравець (178), Коваль (127) and Чумак (67). The using of the word-formative and lexical parallels, phonetic and scriptorthographic variety were by the basic ways of the replenishment of the lexical-semantic group. Originality. In the article the peculiarities of the family names, which made from profession or occupation of the person in the 1756 Register of the Zaporozhian Host, is presented for the first time. In the process of the formation of the family names of Zaporozhian Cossacks the appellatives for designation person’s line occupation enjoyed by comparatively high degree of the anthroponymyzation. Conclusions. About importance of the register as a source of the social-economic history Ukraine and Zaporozhian Sich in particular indicates that fact, that in it keeps the family names for designation about 120 professions and lines occupations, and 106 names, which made from social affiliation, in the connection with military and administrative service and from names of the church posts.